The Tiger Strike Exercise tested the ability and agility of PALAPES UMPSA Cadet Officers - Mohd Azam, Muhammad Akhir; Nurul Fatihah, Allias; Norhaniza, Syafrizal (UMPSA, 2024)
LEPAR, 20 July 2024 - The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), who also serves as the Commander of PALAPES UMPSA, Captain (Honorary), Professor Dato' Ts. Dr. Yusserrie Zainuddin, was on hand to witness the thrilling final attack phase of the exercise for cadet officers.